Pembelajaran Karakter Kepedulian Sosial di Rumah Anak Sholeh Wijaya Karya Patenggangan Air Tawar Barat Kota Padang - Aulia, Rozi; Ismaniar, Ismaniar (JFACE: Journal of Family, Adult, and Early Childhood Education, 2020)
This research is motivated by the phenomenon of the high social concern of the children of the seaside pantenggangan to the Character of Social Concern in Sholeh Wijaya Children's Home, Patenggangan Air Tawar Barat, Padang City. This study aims to describe the learning of social care characters in RAS Wijaya Karya viewed from aspects of learning strategies, learning methods, and forms of learning media used. This type of research is descriptive qualitative using a case study approach. Sources of data in this study consisted of research subjects and research informants. Data collection techniques used were interviews, observation and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The data validity technique uses source triangulation. The results of this study indicate that the social awareness character learning strategy in RAS has four strategies namely; check the feeling / check the child's basic emotions, imagine, activity, and sharing. Furthermore, the method of learning social care characters in RAS has 5 methods namely; learning while playing method, demonstration method, discussion method, lecture method and kauny quranic school method. The third aspect is the social media character learning media in RAS using 6 media namely; dice, paper, books, sticks, cellphones, and mirrors. Suggestions in this research are that RAS managers can develop programs and increase community interest in participating in RAS activities.